Innovation in the Institutional Maturity of Public Universities: Limits and integration of organisational capabilities (Research, Society and Development, 2026)
Innovation in the context of Brazilian public universities manifests less as the result of adopting technologies or multiplying initiatives and more as an expression of the institutional capacity to articulate practices, processes and structures within organisational functioning. This article aims to analyse the role of innovation in institutional maturity, focusing on the limits and organisational conditions that shape its consolidation as an institutional practice. It adopts a qualitative analytical-conceptual approach, grounded in the articulation between specialised literature and the analysis of regulatory frameworks that influence the operation of public universities. The findings indicate that the presence of innovative initiatives does not necessarily imply their incorporation into institutional functioning, as situations of organisational fragmentation, weak coordination between units and difficulties in integrating information flows remain recurrent. The analysis of the regulatory framework shows that innovation develops within a regulated environment marked by requirements of control, transparency and standardisation, which condition its operationalisation. In this context, institutional maturity is not expressed by the number of initiatives, but by the capacity to integrate and sustain them over time. It is concluded that innovation depends on the articulation between organisational capabilities and normative requirements, being shaped by the forms of coordination and integration that structure institutional action.